2013
DOI: 10.21009/jgg.032.02
|View full text |Cite
|
Sign up to set email alerts
|

ANALISIS PENUTUPAN LAHAN DAN PERUBAHANNYA MENJADI KELAPA SAWIT DI INDONESIA (Studi Kasus di 5 Pulau Besar di Indonesia periode 1990 s.d 2010)

Abstract: Indonesia is one of the largest crude palm oil (CPO) producing countries in the world and at the same time have experienced high levels of deforestation. The link between deforestation and expansion of oil palm plantation has been a source of controversy, which has been exacerbated by the lack of objective quantitative information on the nature of land use and land cover change and the expansion of oil palm plantations.  This report provides an independent analysis of land use and land cover change for a broad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Palm oil plantations in Indonesia began to be associated with massive deforestation in the 1990s and 2000s. Many researchers stated that deforestation is caused by the expansion of palm oil plantation: Gunarso et al (2013) and Koh and Wilcove (2008) reported that 52%-79% of Indonesian palm oil plantations carried out deforestation for the establishment of new plantations; Carlson et al (2013) stated that 89%-90% of plantations in Kalimantan were previously forest. The ISPO requirements regarding forest conversion follow the Indonesian regulations.…”
Section: Deforestationmentioning
confidence: 99%
“…Palm oil plantations in Indonesia began to be associated with massive deforestation in the 1990s and 2000s. Many researchers stated that deforestation is caused by the expansion of palm oil plantation: Gunarso et al (2013) and Koh and Wilcove (2008) reported that 52%-79% of Indonesian palm oil plantations carried out deforestation for the establishment of new plantations; Carlson et al (2013) stated that 89%-90% of plantations in Kalimantan were previously forest. The ISPO requirements regarding forest conversion follow the Indonesian regulations.…”
Section: Deforestationmentioning
confidence: 99%
“…Indonesia is the world's largest palm oil producer and is included in the top 10 P&P producers (Pirad et al, 2018), with a plantation area of 10 million ha (FWI, 2014). In 2005-2010, the expansion of oil palm plantations reached 1.3 million ha (Gunarso et al, 2013) and expanded, of which one third came from the conversion of primary and secondary forests. Estimated forest loss in Indonesia in 1996-2000 was 3.51 million ha/year, 2006-2010 reached 0.69 million ha/year (Margono et al, 2014) then decreased to 0.48 million ha/year in 2016(MOEF, 2018 and with ongoing threats to forests.…”
Section: Introductionmentioning
confidence: 99%